2019
DOI: 10.1186/s41256-018-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Artemisinin–based combination therapy among healthcare providers, Lokoja, North-Central Nigeria

Abstract: BackgroundIn Nigeria, Artemisinin-based Combination Therapy (ACT) is the recommended first line antimalarial medicine for uncomplicated malaria. However, health care providers still continue the use of less efficacious medicines such as Sulphadoxine-pyrimethamine and chloroquine. We therefore determined preference for ACT (PFA) and factors associated with PFA among healthcare providers (HCP) in Lokoja, North-Central Nigeria as well as assessed healthcare providers’ knowledge of malaria case management.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Owing to diversity of causes of undernutrition, there is no silver bullet for stunting. To this end, a combination of such nutritional sensitive and specific interventions tailored to the local context can make impact [24, 25]. In the context of Tanzania, socio-demographic disadvantaged populations bear a significant brunt of stunting like other forms of undernutrition [4, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to diversity of causes of undernutrition, there is no silver bullet for stunting. To this end, a combination of such nutritional sensitive and specific interventions tailored to the local context can make impact [24, 25]. In the context of Tanzania, socio-demographic disadvantaged populations bear a significant brunt of stunting like other forms of undernutrition [4, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the role of factors influencing performance of HWs vary with context and environment [24]. Furthermore, health workers’ perception of mRDT [11,17,23] as well as their antimalarial prescription practices also vary with settings [20,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that may have contributed to the slow adoption of the ACTs in the early years following the change in policy especially among public health care professionals included poor understanding of its concept, and cost, amongst others. Just recently, Welle et al (9) reported a low preference for the ACTs (39.6% ) among health care providers in Lokoja, North-Central Nigeria. A closer look at treatment guideline for management of uncomplicated malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, all health care professionals irrespective of cadre or specialty are involved in the treatment of malaria (9). In addition, there is a significant self-management practice among HCPs which may be determined by both medicine factors such as the tolerability profile of the drug, the cost of the medicine as well as personal preference and preconceived ideas about a medicine.…”
Section: Mots-clésmentioning
confidence: 99%